Fibrodysplasia Ossificans Progressiva: Literature Review and Case Report - Natalya N. Korableva; Evgeniy V. Berestnev; Sergey M. Kiselyov; Natalya F. Chipsanova (Вопросы современной педиатрии)
Background. Fibrodysplasia ossificans progressiva (FOP) is a genetic disease of the heterotopic ossification group associated with the mutation in ACVR1/ALK2 gene. FOP is characterized by progressive heterotopic endochondral ossification of connective tissue that occurs in postnatal period. It leads to formation of qualitatively normal bone in extraskeletal areas. Congenital hallux deformity   is typical for this disease. The clinical picture is characterized by aggravations that are usually caused by trauma or viral infections. Formation of Heterotopic ossificate formation can be observed during aggravations. There is no etiological treatment for FOP. Systemic glucocorticosteroids, non-steroidal anti-inflammatory drug (NSAIDs), mast cell stabilisers, antileukotriene drugs and bisphosphonates can be used in these patients.Clinical case description. The child was born with congenital hallux deformity typical for FOP. The disease onset was noted at the age of 2 years 8 months with a tumor-like painful mass on the neck. Oncological (lymphoproliferative) disease was suspected but biopsy from the lesion did not confirm its malignant nature. The child was consulted by pediatric rheumatologist who has diagnosed FOP. Etanercept and zoledronic acid were administrated, though etanercept was later discontinued. For now, the child receives zoledronic acid infusions 2 times per year and daily NSAIDs.Conclusion. The difficulties in FOP diagnosing are associated to its sporadic nature and clinical picture similarity to other diseases. Suspected malignancy leads to biopsy that is highly undesirable in FOP patients due to high risk of iatrogenic complications.